UJI FISIK SEDIAAN SABUN CAIR EKSTRAK ETANOL DAUN MANGROVE (Rhizophora mucronata) - Rasi Fitri Yanti Tuasikal; Irwandi Irwandi; Lukman Hardia (Universitas Pendidikan Muhammadiyah Sorong, 2024)
Caffeic acid, vanillic acid, p-hydroxy benzoic acid, tannins, kau-16-ene, benzophene, phenolic compounds of the flavonoid group, phenolic acids, and dihydroflavonol tannins are all present in mangrove leaves. Alkaloids, coumarins, flavonoids, phenols and polyphenols, quinones, resins, saponins, phytosterols, tannins, xantoprotins, pigments (chlorophyll, carotenoids), and sugars are just some of the substances that can be found in plants. This plant has potential as an antibacterial, antimalarial, antiviral, and antioxidant. The purpose of this study was to obtain the formulation of Mangrove leaf ethanol extract liquid soap preparation and also know the physical properties of black mangroves leaf extract liquid soap preparation. In this study, physical tests of preparations such as organoleptic tests, pH tests, viscosity tests, and foam height tests were carried out. The results in organoleptic test research meet SNI standards, the Ph test has a high pH value of F1 12.71, the dosage properties become more alkaline, the viscosity test results meet SNI standards, while for the high test F3 foam has a high value of 84.91 so that it exceeds the SNI standard.